State of the union : a century of American labor - Lichtenstein, Nelson (Politics and society in twentieth-century America., 2013)
In a fresh and timely reinterpretation, Nelson Lichtenstein examines how trade unionism has waxed and waned in the nation's political and moral imagination, among both devoted partisans and intransigent foes. From the steel foundry to the burger-grill, from Woodrow Wilson to John Sweeney, from Homestead to Pittston, Lichtenstein weaves together a compelling matrix of ideas, stories, strikes, laws, and people in a streamlined narrative of work and labor in the twentieth century.